If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(8x + -7) + 18x = 31x + -1(90x + 28x) + -45 Reorder the terms: 5 + -1(-7 + 8x) + 18x = 31x + -1(90x + 28x) + -45 5 + (-7 * -1 + 8x * -1) + 18x = 31x + -1(90x + 28x) + -45 5 + (7 + -8x) + 18x = 31x + -1(90x + 28x) + -45 Combine like terms: 5 + 7 = 12 12 + -8x + 18x = 31x + -1(90x + 28x) + -45 Combine like terms: -8x + 18x = 10x 12 + 10x = 31x + -1(90x + 28x) + -45 Combine like terms: 90x + 28x = 118x 12 + 10x = 31x + -1(118x) + -45 Remove parenthesis around (118x) 12 + 10x = 31x + -1 * 118x + -45 Multiply -1 * 118 12 + 10x = 31x + -118x + -45 Reorder the terms: 12 + 10x = -45 + 31x + -118x Combine like terms: 31x + -118x = -87x 12 + 10x = -45 + -87x Solving 12 + 10x = -45 + -87x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '87x' to each side of the equation. 12 + 10x + 87x = -45 + -87x + 87x Combine like terms: 10x + 87x = 97x 12 + 97x = -45 + -87x + 87x Combine like terms: -87x + 87x = 0 12 + 97x = -45 + 0 12 + 97x = -45 Add '-12' to each side of the equation. 12 + -12 + 97x = -45 + -12 Combine like terms: 12 + -12 = 0 0 + 97x = -45 + -12 97x = -45 + -12 Combine like terms: -45 + -12 = -57 97x = -57 Divide each side by '97'. x = -0.587628866 Simplifying x = -0.587628866
| 3(X+6)=2(X-2) | | 6+12x=-5+5 | | 6(a+3)-10=-2(a+8) | | 3(x-8)=6(x+3) | | 6(a+3)-10=-2a+8 | | 10x+224-14x=188 | | X*x*7=63 | | 11=6m-1 | | W+48=-95 | | 8t^2+4t=0 | | 1-2(6-y)=y | | 10x-8=3x+3 | | 0.2z=3z | | -21b+10a=120 | | 4y+11=13 | | 3x+16-8x=19-14x+9x-3 | | 34g+17= | | X-45=108 | | 10a-21b=120 | | 700x^2+100x-16=0 | | 65-y=256 | | y=x^4-x^3+x^2-8 | | 6s-12=42s | | 6x+3y=2x+3 | | 6x+108=11-12 | | x*x+18=22 | | 4y+11=3y+4x | | (4a^2-3a+4)-(3a^2-7a+6)= | | (3a-7)+(4a+5)= | | 2(2x+3)=3(x-10) | | (2x+4)+(8x+6)=90 | | 3n-5=-48+-4n |